Transformation of KUA Counselor Competencies in Bone Regency Through the Implementation of the Scientific Mediation Practical Module - Suryo Husnul Syukur (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2026)
Family counseling services at the Bone Regency Office of Religious Affairs (KUA) currently face a critical obstacle in the form of low mediation effectiveness due to the lack of applicable technical instruments. This policy research aims to analyze the correlation between the lack of a practical module and the limited competence and quantity of counselor Human Resources (HR). The main problem identified is the dominance of normative-theological training curricula, resulting in staff lacking applied psychology skills in handling complex domestic conflicts. The policy methodology used in this study is a descriptive-prescriptive policy analysis with a qualitative approach, where primary data were obtained through observation and a literature review on HR management within the Ministry of Religious Affairs. An analysis of alternative policies was conducted using William N. Dunn's evaluation criteria, which include effectiveness, feasibility, and impact. The analysis results indicate that developing a scientific mediation practical module is the most fundamental solution to shift service patterns from mere advice to measurable clinical interventions. As a primary recommendation, this policy proposes the issuance of a Decree of the Director General of Islamic Community Guidance concerning Technical Guidelines for the Implementation of the Mediation and Applied Psychology Practical Module as a requirement for graduation from technical training.